Optimal ice thermal energy storage charging operation of chiller plant during off-peak hours - Shaari, S.R.; Othman, Mohammad Lutfi; Veerasamy, Veerapandiyan; Dahlan, Nofri Yenita; Ramachandran, Rajeswari; Chik, Mohd Hanafiah; Hizam, Hashim; Zainal Anuar, Suhafizudin (School of Engineering, Universiti Teknologi MARA (UiTM), Malaysia, 2021)
A chiller plant (CHIP) consumes high electrical energy when high cooling thermal is required to be charged into ice thermal energy storage (ITES). This is because the electrical energy consumption of a chiller is proportional to cooling thermal. Therefore, this study aims to reduce energy consumption, E (kWh) of CHIP to charge ITES tank by using Linear Programming (LP). This technique may investigate the optimal operating period (OP) of chillers and other auxiliary equipment for ITES charge during the off-peak hour. Then, energy consumption, E (kWh) of CHIP resulted through this optimization technique support is compared to CHIP loading for ITES charge without using optimization technique. Results showed that energy saving of 11.25% was probably achieved by using optimization technique compared to ITES charging without using optimization technique.